SISTEM INFORMASI PEMBAYARAN SPP PADA SMK SWASTA TELADAN TANAH JAWA MENGGUNAKAN VB.NET - Heru Sugara; Erwin Sirait; M. Ali Hanafiah; Nancy Florida Siagian (Politeknik Bisnis Indonesia, 2020)
The purpose of this study was to design a tuition payment accounting information system using Vb.Net which aims to simplify and accelerate the Teladan Tanah Jawa private vocational school in processing school fee payment data. The research method used in this research is observation, interview, sampling, and literature study. The analysis tools used are Data Flow Diagrams (DFD), Entity Relationship Diagrams and the relationships between tables. This information system makes it easier for the school administration to find student data, process arrears data, data on daily school fees and reports on tuition payments.